The beyond - Neill, Chloe (A devil's isle novel, 2019)
To save the city she loves, Claire Connolly must cross the border into the unknown.... It's been nearly a year since the Veil between the human world and the Beyond was torn apart and war began again. Sensitive Claire Connolly and bounty hunter Liam Quinn have been helping their human and Paranormal allies fight back against the ravaging invaders and save what is left of New Orleans. But a new enemy--more powerful than any Claire and Liam have seen before--has arisen, and even Devil's Isle cannot hold her.... When Claire learns of a new magical weapon--one built by Paranormals--she knows it could turn the tide of the war. But to reach it, she and Liam will have to cross into the Beyond itself. In a world full of hostile magic and dangerous foes, she'll have to channel the powers she once kept hidden in order to survive. New Orleans hangs in the balance, and the storm is growing closer....